Pandemic COVID 19 and healthcare professionals: Mental health impact and depression - Ben Soussia, R.; Melki, R.; Aoun, M. H.; Bouali, W.; Zarrouk, L. (European psychiatry, 2023)
Introduction The SARS-COV2 pandemic represents a problematic and disruption of global health. Repeated exposure to stressful situations leads to increased psychological distress. Objectives To determine the psychoaffective impact of the Covid-19 pandemic on the mental health of health professionals in Tunisia, assess the intensity of depressive symptoms professionals and determine factors associated with the development of these symptoms. Methods This was a multicenter, cross-sectional, descriptive and analytical study conducted among health professionals, from May 2nd, 2020 to June 30th, 2020 in Tunisia. The health professionals included were physicians, nurses, dentists, and pharmacists. Using an electronic form << Google Form >>, a questionnaire was drawn up with 32 items. Assessment of depressive symptoms was performed using the PHQ-9 psychometric scale. Statistical analysis was performed using SPSS 21.0 statistical software. Regarding the analytical study, a professional with a PHQ-9 scale score between 10 and 27 was considered as having moderate to severe depressive symptoms while a score between 15-27 was in favor of severe depressive symptoms. Results Caregivers were predominantly female 69.5% with a mean age of 30.74 years. Anxiety-depressive psychiatric history was found in 11.8% of the subjects. The majority of the professionals were doctors (77.8%) and 9.4% of the participants were nurses. The majority of participants worked in university hospitals (84.2%). One third of the participants, (34.3%) worked in departments with Covid-19 patients with respective rates of 57% for nurses and 36% for physicians. Dentists and pharmacists did not work in Covid-19 circuits. The mean score on the PHQ-9 scale was equal to 8.62 ± 5.35. Depressive symptoms were noted in 37.4% of the professionals, with moderate to severe intensity in 35.5% of cases. Participants with a psychiatric history of depression or anxiety disorder had significantly higher depressive symptom scores (p<0.001) with 6 times higher the risk of developing moderate to severe depressive symptoms (p<0.0001, OR 6.25, CI [2.35-16.61] and almost 3 times higher the risk of experiencing severe depressive symptoms (p=0.05, OR=2.93, CI [1.09-7.88]). The nursing profession had high odds ratios for the occurrence of moderate to severe depressive symptoms (p=0.002, OR=4.41, CI [1.58-12.28]) and severe depressive symptoms (p=0.02, OR=3.82, CI [1.28-11.39]). A significant relationship was established, between the development of depressive symptoms of moderate to severe intensity with the history of depressive disorder or anxiety disorder (p=0.001) and the nursing profession (p=0.01). Conclusions The optimization of prevention, the creation of specific treatment, the promotion of health education and specific hygiene rules would participate in improving the mental health of health professionals. Disclosure of Interest None Declared